The Use of Team Games Tournament (TGT) trough Crossword Puzzle to Improve Vocabulary Mastery of Eighth Grade Students at SMPN 19 Mataram - Hikmah, Lailatul; Farmasari, Santi; Susanti, Ni Wayan Mira (Journal of Authentic Research, 2025)
Vocabulary mastery is fundamental to the development of the four core language skills—listening, speaking, reading, and writing—yet many learners struggle due to limited exposure and practice. This study investigates the effectiveness of integrating Team Games Tournament (TGT), a cooperative learning strategy that fosters active participation and peer support, with crossword puzzles, a game-based learning tool that promotes vocabulary recall and contextual understanding, in improving the vocabulary mastery of eighth-grade students at SMPN 19 Mataram. Using a quasi-experimental one-group pre-test–post-test design, 30 purposively selected students were given a vocabulary test consisting of 50 multiple-choice and 10 fill-in-the-blank items on descriptive adjectives before and after the treatment. Over two sessions (2×45 minutes), students participated in TGT activities embedded with crossword puzzles, enabling them to review and apply new vocabulary collaboratively in a competitive yet enjoyable setting. Results showed a significant improvement in mean scores from 58.33 (SD = 7.38) on the pre-test to 83.00 (SD = 5.91) on the post-test. A paired sample t-test confirmed the significance of this improvement (t(29) = 21.77, p < 0.05). These findings align with prior research on cooperative and game-based learning, suggesting that TGT combined with crossword puzzles not only enhances vocabulary acquisition but also boosts student engagement, motivation, and classroom collaboration.